Optimization of media composition for bioprotein production from empty fruit bunch by Aspergillus Terreus UniMAP AA-1 - Norazira Ali (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Two steps optimization strategy based on stastisical experimental design was carried out to enhance bioprotein production by solid state fermentation utilizing empty fruit bunch (EFB) as substrate. Plackett-Burman design was employed first where 7 variables were studied for their influence in bioprotein production. NH4NO3, CuSO4.5H2O and MgSO4.7H2O were found to be most significant variables for improving bioprotein production. Central Composite Design (CCD) was employed to maximize the production of bioprotein. A mathematical model was developed to show the effects of each media component and their combinatorial interaction on bioprotein production. The optimal medium composition for maximum bioprotein production was are 0.70% (v/w) of inorganic nitrogen source (NH4NO3), 0.06% (v/w) of magnesium source (MgSO4.7H2O) and 0.23% (v/w) of copper source (CuSO4.5H2O). Validation fermentation was carried out to validate the model.From the model validation process, predicted amount of protein concentration produced was 0.606598 mg/mL which is slightly higher than the experimental run in CCD which was 0.604 mg/mL.